26. KNOWLEDGE, ATTITUDE OF HEALTH STUDENTS AT DAI NAM UNIVERSITY ABOUT MONKEYPOX IN 2022 (Vietnam Journal of Community Medicine, 2023)
Objectives: To describe knowledge and attitudes of health students at Dai Nam University aboutmonkeypox in 2022.Methods: Cross-sectional study.Results: The study was conducted on 661 students of the Faculty of Medicine, the Faculty ofPharmacy and the Faculty of Nursing, Dai Nam University using a pre-designed questionnaire todescribe students’ knowledge and attitudes about monkeypox. The results showed: the rate of gainingknowledge about monkeypox was 56.4%. The percentage of students with a positive attitude aboutmonkeypox was 52%.Conclusion: The rate of gaining knowledge about monkeypox as well as the percentage of studentswith positive attitude about the disease is low. Therefore, the school administration needs to takepositive and specific measures to contribute to improving students’ knowledge and attitudes aboutmonkeypox.
Keywords: Knowledge and attitude, monkeypox.